Pemberian Media Photonovela Meningkatkan Pemahaman Isi Informed Consent Pada Pasien Sectio Caesaria di RSIA HST Trenggalek - Dewangga Primananda Susanto; Harun Al Rasyid; Lukman Hakim (Universitas Muhammadiyah Yogyakarta, 2017)
The aim of this research is to know the effect of traditional comic strip photo novella media on the level of informed understanding of patient of Sectio Caesarea (SC). This research is a quasi-experimental research by dividing the research subjects into two groups namely the treatment group (given photo novella) and control (not given photo novella) each of 30 people in RSIA HST Trenggalek hospital. This study found that group understanding received significantly higher media in terms of explanation of indications, procedures, objectives, alternatives, risks, complications and SC costs compared to patients without photo novella media. There were no significant differences in terms of explanation of action names and SC prognosis in both groups.